Imaging of the B2 Glenoid: An Assessment of Glenoid Wear. (July 2019) - Mahylis, Jared M; Entezari, Vahid; Jun, Bong-Jae; Iannotti, Joseph P; Ricchetti, Eric T
Background: Glenohumeral osteoarthritis (OA) carries a spectrum of morphology and wear patterns of the glenoid surface exemplified by complex patterns such as glenoid biconcavity and acquired retroversion seen in the B2 glenoid. Multiple imaging methods are available for evaluation of the complex glenoid structure seen in B2 glenoids. The purpose of this article is to review imaging assessment of the type B2 glenoid. Methods: The current literature on imaging of the B2 glenoid was reviewed to describe the unique anatomy of this OA variant and how to appropriately assess its characteristics. Results: Plain radiographs, magnetic resonance imaging, and standard 2-dimensional computed tomography (CT) have all shown acceptable assessments of arthritic glenoids but lack the detailed and highly accurate evaluation of bone loss and retroversion seen with 3-dimensional CT. Conclusion: Accurate preoperative identification of complex B2 pathology on imaging remains essential in planning and achieving precise implant placement at the time of shoulder arthroplasty.